Extreme anti-interference capability in temporal and frequency domain by utilizing laser Antenna in optical wireless communication system - Kun Qian; Hongyu Yang; Jingzhou Li; Dong Liang; Jiaxi Li; Yichi Zhong; Zhuhua Xu; Jiahao Zhang; Hanhuai Yang; Xizhe Liang; Junping Zhang; Hongxing Dong; et al. (PhotoniX)
Abstract Fluorescent antennas have emerged as promising alternatives to conventional lens modules in optical wireless communication (OWC) systems, offering an expanded field of view (FOV) by surpassing the étendue limit. However, their limited anti-interference performance in both time and frequency domains has constrained their widespread applications. Herein, we introduce a novel “laser antenna” that integrates stimulated emission from high-quality perovskite microlasers into the optical antenna design. Achieving a theoretical bandwidth of up to 36.2 GHz and a signal-to-noise ratio (SNR) of up to 40 dB, this laser antenna demonstrates strong anti-interference capabilities in the temporal domain. Furthermore, spectral analysis using amplitude shift keying (ASK) modulation reveals its distinct periodicity, tunability, and recoverability, enabling robust frequency selectivity even in the presence of interference. These findings establish the laser antenna’s potential to overcome critical limitations of conventional OWC systems, thereby paving the way for efficient, stable, and high-performance optical wireless links.